High levels of molasses and peanut hulls in a urea supplemented diet for sheep fattening - El-Khidir, O.A.; Khalafallah, A.M.; Gumaa, A.Y; Osman, O.K. (1984)
A two-phase experiment was conducted to study the effects of feeding molasses (M) or sorgum (S) based diet on feedlot performance and carcass analysis of 48 intact sudndesert male lambs (age 3-7 months) divided equally into groups of a heavy (H) and light (L) with an average 27±0.8 kg and 31.9±0.4 kg starting liveweight respectively; at central animal production and research station at Kuku, Sudan. In the first phase of the experiment the analysis were divided according to liveweight and diet offered into four groups of 12 lambs each and were raised to an average 40 kg. Slaughter weight on either diet. Daily liveweight gain for HM, HS, LM and LS were 204, 236,209 and 219g respectively, where as dressing percentage were 44.1, 44.8, 43.5 and 48.21. Respectivelly for six lambs form each group LM and LS were 153 and 186g/day and dressing percentage of these lambs were 49.4 and 50.7% respectively during the second experimental phase using the remaining six lambs continuing on their same diet to a maximum of 48 kg finishing weight. No significant differences were observed between the diet treatments in feedlot performance or carcass analysis data. It was concluded that fattening desert lambs to 40 kg finishing liveweight has high feed conversion efficiency and yielded a desirable carcass of moderate fat percentage.